Flagellin as a vaccine adjuvant - Baofeng Cui; Xinsheng Liu; Yuzhen Fang; Peng Zhou; Yongguang Zhang; Yonglu Wang (Expert Review of Vaccines, 2018)
Introduction: Bacterial flagellin, as a pathogen-associated molecular pattern (PAMP), can activate both innate and adaptive immunity. Its unique structural characteristics endow an effective and flexible adjuvant activity, which allow the design of different types of vaccine strategies to prevent various diseases. This review will discuss recent progress in the mechanism of action of flagellin and its prospects for use as a vaccine adjuvant. Areas covered: Herein we summarize various types of information related to flagellin adjuvants from PubMed, including structures, signaling pathways, natural immunity, and extensive applications in vaccines, and it discusses the immunogenicity, safety, and efficacy of flagellin-adjuvanted vaccines in clinical trials. Expert commentary: It is widely accepted that as an adjuvant, flagellin can induce an enhanced antigen-specific immune response. Flagellin adjuvants will allow more effective flagellin-based vaccines to enter clinical trials. Furthermore, vaccine formulations containing PAMPs are crucial to exert the maximum potential of vaccine antigens. Therefore, combinations of flagellin-adjuvanted vaccines with other adjuvants that act in a synergistic manner, particularly TLR ligands, represent a promising method for tailoring targeted vaccines to meet specific requirements.